Trusted systems : 7th International Conference, INTRUST 2015, Beijing, China, December 7-8, 2015, Revised selected papers /: 7th International Conference, INTRUST 2015, Beijing, China, December 7-8, 2015, Revised selected papers. (2016) - Unknown
No abstract available